Challenges and perspective of recent biomass pretreatment solvents - 김광호; Chang Geun Yoo (Frontiers Media S.A., 2021)
The increased demands on renewable and sustainable products require enhancing the current conversion efficiency and expanding the utilization of biomass from a single component (i.e., cellulose) to entire biomass components in the biorefinery concept. Pretreatment solvent plays a critical role in various biorefinery processes. Recent pretreatment solvents such as organic co-solvents, acid hydrotropes, ionic liquids and deep eutectic solvents showed effective biomass fractionation as well as preservation of high-quality cellulose and lignin under mild conditions. Despite these significant enhancements in biomass pretreatment solvent, there are still many challenges, such as feedstock variety, valorization of non-cellulose components, and eco-friendliness of the applied catalyst and solvent. These technical, economic and environmental obstacles should be considered in future biomass pretreatment solvents. In particular, the development of feedstock-agnostic solvent with high fractionation performance for high quality and quantity of all three major components (i.e., cellulose, hemicellulose, and lignin) together would be an ideal direction.